The effect of sandstorms and air pollution on cause-specific hospital admissions in Taipei, Taiwan. Issue 2 (11th July 2007) - Bell, M L; Levy, J K; Lin, Z
Abstract : Objective: Relatively little research exists focusing on the impact of air pollution on hospital admissions in Asia compared to the extensive work conducted in the USA and Europe. The issue is of particular importance because of the frequency, intensity and health effects of Asian sandstorms. This work investigates the relation between cause-specific hospital admissions and sandstorms and air pollution in Taipei, Taiwan's capital. Methods: Time-series analyses of asthma, pneumonia, ischaemic heart disease and cerebrovascular disease hospital admissions were performed for Taipei. An eight-year time period (1995–2002) was considered for various indicators of sandstorms and the pollutants NO2, CO, ozone, SO2, PM10, and PM2.5 . Pollution effects based on single-day lags of 0, 1, 2 and 3 days were explored, along with the average of the same day and previous three days (L03). Results: The risk of ischaemic heart disease admissions was associated with several sandstorm metrics, including indicators of high PM10 levels in the Taipei area, indicators of high PM10 at a monitor designed to measure background pollution, the PM coarse fraction, and the ratio of PM10 to PM2.5 . However, the lag structure of effect was not consistent across sandstorm indicators. Hospital admissions for this disease were 16–21% higher on sandstorm days compared to other days. This cause was also associated with transportation-related pollutants, NO2, CO and PM2.5 . Asthma admissions rose 4.48% (95% CI 0.71% to 8.38%) per 28 μg/m 3 increase in L03 PM10 levels and 7.60% (95% CI 2.87% to 12.54%) per 10 ppb increase in L03 ozone. Cerebrovascular disease admissions were associated with PM10 and CO, both at lag 3 days. SO2 exhibited no relation with admissions. Conclusions: Risk of hospital admissions in Taipei may be increased by air pollution and sandstorms. Additional research is needed to clarify the lag structure and magnitude of such effects.